2016
DOI: 10.1620/tjem.238.131
|View full text |Cite
|
Sign up to set email alerts
|

D-Allose Inhibits Cancer Cell Growth by Reducing GLUT1 Expression

Abstract: Glucose is a major energy source for mammalian cells and is transported into cells via cell-specific expression of various glucose transporters (GLUTs). Especially, cancer cells require massive amounts of glucose as an energy source for their dysregulated growth and thus over-express GLUTs. d-allose, a C-3 epimer of d-glucose, is one of rare sugars that exist in small quantities in nature. We have shown that d-allose induces the tumor suppressor gene coding for thioredoxin interacting protein (TXNIP) and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…GLUT1 is a major player in glucose metabolism in cancer biology, which is usually up-regulated in different types of cancers. 16 Overexpression of GLUT1 not only accelerated glucose metabolism but also protected cancer cells from glucose deprivation-induced oxidative stress. 17 GLUT1 expression inhibition is considered to be a therapeutic target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1 is a major player in glucose metabolism in cancer biology, which is usually up-regulated in different types of cancers. 16 Overexpression of GLUT1 not only accelerated glucose metabolism but also protected cancer cells from glucose deprivation-induced oxidative stress. 17 GLUT1 expression inhibition is considered to be a therapeutic target for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Third, apoptosis could be induced by D-allose (7), however, apoptosis may not appear in all types of cells (3). Fourth, D-allose can inhibit glucose transporter expression and glucose uptake in several human cancer cell lines (9). Some of the above mechanisms of the antitumour effect of D-allose could be associated with regulating expression of thioredoxin and TXNIP, that is, redox status in the broader sense.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that D-allose has growth inhibitory effects in several kinds of malignancies including hepatocellular carcinoma, prostate, ovarian, and head and neck cancers, and leukaemia (3)(4)(5)(6)(7)(8)(9). However, the effect of D-allose on lung cancer progression has not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound, a C-3 epimer of d-glucose with 80% of the sweetness of sucrose, exists in small quantities in nature. This compound is known to possess anticarcinogenic properties via upregulation of thioredoxin interacting protein (TXNIP) [166]. A study involving breast adenocarcinoma, hepatocellular carcinoma, and neuroblastoma cell lines concluded that d-allose downregulates GLUT1 expression and consequently glucose uptake, thus suppressing cancer cell growth, as a result of overexpression of TXNIP [166] (Table 3).…”
Section: D-allosementioning
confidence: 99%